Treatment of Eceng Gondok Waste into Electrical Based on Microbial Fuel Cell - Hijrah Amaliah Azis; Ardiansa Ardiansa; Riki Kusuma Purnama (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2022)
The increasing consumption of electrical energy and still dependent on non-renewable energy has encouraged the implementation of effective, efficient, and environmentally friendly technologies to produce electrical energy. Microbial Fuel Cell (MFC) is one of the alternative technologies that utilize microorganisms in converting chemical energy from organic compounds under anaerobic conditions to be converted into electrical energy. The study was conducted to determine the potential of electrical energy generated from the treatment of eceng gondok waste (Eichhornia crassipes) with variations in the addition of buffer solutions and combinations of electrolyte solutions using the microorganism Saccharomyces cerevisiae through Microbial Fuel Cell technology. This study consists of three stages and methods, namely sample preparation, MFC media preparation, and analysis of pH, current, voltage, and power density. Measurement of the value of the maximum voltage, maximum current and power density is carried out every 3 hours for 27 hours for each treatment. The results were obtained as follows consecutively: firstly, for variations without the addition of buffers and electrolyte solutions are 0.25 volts; 0.08 mA; 13.05 mW/m2, secondly, with buffer and electrolyte solution KMnO4 0.2 M are 1.12 volts; 0.77 mA; 562.92 mW/m2, and thirdly, with buffer and K3Fe(CN)6 0.2 M are 0.47 volts; 0.48 mA; 147.26 mW/m2. Based on the results of the study, it was concluded that the most optimal variation in producing electrical energy was in the variation in the addition of a phosphate buffer and 0.2 M KMnO4 solution. Eceng gondok waste has the potential to be used as a source of electrical energy.